Topical issues of legal regulation of increasing the authorized capital of a joint-stock company in Uzbekistan - Bekzod Umarov (Genius Journals, 2022)
This article studies the theoretical and practical issues of legal regulation of joint-stock companies, the legal regime of the authorized capital of joint-stock companies, and also indicates the main directions for improving the legal regulation of increasing the authorized capital of joint-stock companies in the Republic of Uzbekistan. At the same time, current problems in the legal regulation of increasing the authorized capital of joint-stock companies and the role of shareholders in this direction are analyzed from the standpoint of the comparative legal aspect of developed legal systems.
Keywords: Joint-stock company; authorized capital; shareholders; direction